Antimicrobial Activity of Films and Coatings Containing Lactoperoxidase System: A Review - Yousefi, Mojtaba; Nematollahi, Amene; Shadnoush, Mahdi; Mortazavian, Amir M.; Khorshidian, Nasim (Frontiers in Nutrition, 2022)
Production of safe and healthy foodstuff is considered one of the most important challenges in the food industry, and achieving this important goal is impossible without using various processes and preservatives. However, recently there has been a growing concern about the use of chemical preservatives and attention has been focused on minimal process and/or free of chemical preservatives food products. Therefore, researchers and food manufactures have been induced to utilize natural-based preservatives such as antimicrobial enzymes in their production. Lactoperoxidase, as an example of antimicrobial enzymes, is the second most abundant natural enzyme in the milk and due to its wide range of antibacterial activity, it could be potentially applied as natural preservative in various food products. On the other hand, due to diffusion of lactoperoxidase into the whole food matrix and its interaction and/or neutralization with food components, the direct use of lactoperoxidase in food can sometimes be restricted. In this regard, lactoperoxidase can be used as a part of packaging material, especially edible and coating, to keep its antimicrobial properties to extend food shelf-life and food safety maintenance. Therefore, this study aims to review various antimicrobial enzymes and introduce lactoperoxidase as natural antimicrobial enzyme, its antimicrobial properties and its functionality in combination with edible film to extend the shelf-life of food products.